The Manchester School : Practice and Ethnographic Praxis in Anthropology. - Evens, T. M. S. (Terry) (Berghahn Books, 2006)
Pioneered by Max Gluckman to demonstrate the way in which social practice and structure together constitute and are themselves constituted by the situational flow of social life, the extended case method became diagnostic of the Manchester School of Social Anthropology. Anticipating practice theory, and implicitly politically charged, it was developed as a tool to bring into account what orthodox structural functionalism was ill-equipped to address, namely, problems such as change, conflict, deviance, and individual choice. Edited by two students of Gluckman, the volume comprises repr.